HNF1A and A1CF coordinate a beta cell transcription-splicing axis that is disrupted in type 2 diabetes - Bernardo, Edgar; De Vas, Matías Gonzalo; Balboa, Diego; Cuenca-Ardura, Mirabai; Bonàs-Guarch, Sílvia; Planas-Fèlix, Mercè; Mollandin, Fanny; Torrens-Dinarès, Miquel; Maestro, Miguel Angel; García-Hurtado, Javier; Moratinos, Sonia; Ravassard, Philippe; et al. (Cell metabolism, 2025)
Type 2 diabetes (T2D) is a devastating chronic disease marked by pancreatic β cell dysfunction and insulin resistance, whose pathophysiology remains poorly understood. HNF1A, which encodes transcription factor hepatocyte nuclear factor-1 alpha, is the most commonly mutated gene in Mendelian diabetes. HNF1A also carries loss- or gain-of-function coding variants that respectively predispose to or protect against polygenic T2D. The mechanisms underlying HNF1A-deficient diabetes, however, are still unclear. We now demonstrate that diabetes arises from β cell-autonomous defects and identify direct β cell genomic targets of HNF1A. This uncovered a regulatory axis where HNF1A controls transcription of A1CF, which orchestrates an RNA splicing program encompassing genes that regulate β cell function. This HNF1A-A1CF transcription-splicing axis is suppressed in β cells from T2D individuals, while genetic variants reducing pancreatic islet A1CF are associated with increased glycemia and T2D susceptibility. Our findings, therefore, identify a linear hierarchy that coordinates β cell-specific transcription and splicing programs and link this pathway to T2D pathogenesis.